(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
A family’s health is guaranteed by a healthy woman. Ayurveda and contemporary medicine have both discussed the idea of a healthy yoni at various stages of a woman’s life, from adolescence to menopause. These days, vaginal infections are a major concern for people of all ages and socioeconomic backgrounds. Because women have a special role of giving birth, gynecological illnesses have gained enormous relevance in the medical field. The majority of gynecological problems are included under the word "Yonivyapad," which is used in Ayurveda to refer to women’s health care. Among 20 Yoni Vyapath’s Kaphaja yonivyapath is the one which is due to vitiation of Kapha, this vitiated Kapha reaches the Yoni Pradesha causes signs and symptoms like Kandu, Picchila Srava and Alpa Vedana as well as Sthanika and Sarvadaihika Kapha Prakopa Laxana. The treatment of Kaphaja Yonivyapath explained in classic as Kapha hara Dravyas and Shodhana Chikitsa mainly Vamana is indicated. This can be correlated with vulvovaginitis which is caused due to bacterial vaginosis, moniliasis and trichomans vaginalis. In this review an attempt has been made in this work to provide a conceptual analysis that covers nearly all of the Nidana, Samprapti and Chikitsa of Kaphaja Yoni Vyapad according to both Ayurveda and modern.